Navigating Difficult Times with Pillow Talk: Post Sex Communication as a Strategy for Mitigating Uncertainty Following Relational Transgressions. (4th May 2018) - Denes, Amanda; Crowley, John P.; Makos, Shana; Whitt, Joseph; Graham, Kirsten
Abstract : The present study extends previous work on communication after sexual activity by investigating the influence of "pillow talk" over time within relationships that have experienced a recent transgression. Thirty-six participants who had experienced a transgression committed by a current dating partner provided information about their levels of relational uncertainty, amount of pillow talk, and relational outcomes. Findings revealed that, over the course of a month, increased changes in pillow talk were negatively associated with uncertainty and positively associated with several relational outcomes. Self and relationship uncertainty also mediated the associations between pillow talk and several relational outcomes. These results provide insight into how pillow talk might play a protective function in helping dating partners manage uncertainty following a relational transgression.